Law Enforcement against Children’s Criminal Action Based On Law Number 11 of 2012 Concerning Children Criminal Justice Systems (International Journal of Scientific Research and Management (IJSRM), 2020)
This research was conducted to analyze and find out how criminal law policy is in the effort to apply criminal sanctions against children facing the law in terms of Law No. 11 of 2012 concerning the Criminal Justice System for Children and whether the concept of Diversity can be applied in the process of law enforcement against children involved in Narcotics Crimes. This research is a normative study, to analyze the legal material related to the problem under study, the author uses the Interpretation, Subjective and Objective Interpretation instruments, after that the authors process these legal materials by deductive thinking. The results obtained from the study that the drafting of Law Number 11 of 2012 is a replacement to Law Number 3 of 1997 concerning juvenile justice conducted with the aim of establishing a judiciary that truly guarantees the best protection of the interests of children facing the law as nation’s next generation. The concept of Restorative Justice is one of the important things in Law Number 11 of 2012 where restoring the situation as it used to be the main goal and also no less important is the form of criminal sanctions that can be imposed on Children where criminal sanctions that are harsh and miserable are used as ultimum Remedium is not as a premium remedium especially as a maximum remedium. The concept of diversion that should be applied in Indonesia in the future, should be a combination of the concept of diversion that is applied in Australia, namely Police Diversion which is combined with the process of handling cases with the diversion prevailing in Indonesia today.